Implementing Character Education through School Religious Culture: Implications from Bangsal 1 Public Senior High School, Mojokerto - Fathullah, Muhamad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the implementation and implications of character education based on School Religious Culture at SMAN 1 Bangsal Mojokerto. The moral degradation of adolescents marked by increasing deviant behavior demands character education that not only teaches knowledge but also shapes morals through exemplary behavior and habituation of noble values. This research uses a qualitative approach with a case study design. Data collection techniques were conducted through non-participatory observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and data verification. Data validity was tested using method triangulation. The results show that the implementation of character education based on School Religious Culture at SMAN 1 Bangsal includes: (1) Structured and sustainable implementation of religious culture, (2) Integration of religious values in school life, (3) Habituation of character values from the beginning, (4) Active role of religious organizations (UKKI), and (5) Inclusive attitudes and tolerance towards non-Muslim students. The identified implications are: (1) Formation of disciplinary character, (2) Strengthening of religious character, (3) Development of responsibility character, (4) Growth of leadership character, and (5) Formation of tolerance character. This research confirms that the School Religious Culture approach is effective in shaping students' character holistically and can be replicated in other schools with similar characteristics.